The Effect of Self-Efficacy on the Self Directed Learning of Junior High School Students - Yoselisa, Dani - (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Abtract: The beginning of the first year at the junior high school level is a very difficult moment for many students because students have to many challenges such as: changes in the school environment, cognitive, psychological and social. This challenge requires students to be able to excel academically in terms of student learning independence or self-directed learning, namely the ability of students to understand lessons, set learning strategies, self-regulate, and evaluate their performance, which has an impact on decreasing learning success. The purpose of the study was to see the effect of self-efficacy on the self-directed learning of junior high school students. The sample of this study was class VIII students with a total of 105 students using random sampling technique. The method used is descriptive analysis and simple linear regression. The results showed that self-efficacy affects self-directed learning of junior high school students.